Finite element method for engineers from theory to practice - Vallabhan, C. V. G. (Alpha Science International, 2011)
Emphasizing problems in solid mechanics with numerous examples, this book explains the theory in four fundamental steps with a flow chart to develop equations for the finite element models and the associated computer programs.